Diagnosis and management of syphilis infection in pregnancy: a literature review - I Gde Sastra Winata; William Alexander Setiawan; Ni Luh Wita Astari Widhusadi; DPG Jananuraga Maharddhika; Fenyta Christyani; Putu Bagus Darmayasa; Anthony Stephen Halim; Ernest TB Sianturi (Indonesian Journal of Perinatology, 2023)
Treponema pallidum, which causes the infectious disease syphilis, has a high rate of vertical transfer from mother to kid. Untreated maternal infection increases the risk of perinatal morbidity and mortality and unfavorable pregnancy outcomes, notably congenital syphilis. It is necessary to check for gestational syphilis during the prenatal period, and its diagnosis is straightforward. Nevertheless, this illness still affects two million pregnant women globally, indicating its significant prevalence. Congenital syphilis clinical symptoms are regulated by gestational age, maternal syphilis stage, maternal therapy, and fetus immune response. Early and late congenital syphilis have historically been used to describe it. The direct identification of treponemes, serological tests, and clinical signs all contribute to the diagnosis of maternal infection. Penicillin is typically used in the treatment, which also includes sexual partners. Fetal infection can be treated and prevented from spreading from the mother to the fetus with proper maternal infection management. To lower the prevalence of congenital syphilis, screening, early detection, and appropriate care are crucial during pregnancy and the preconception period.